LITERATURE REVIEW ON ARMAMENT TECHNOLOGY, CAUSES, STRATEGIES, AND FUTURE PROJECTIONS: RUSSIA-UKRAINE WAR CASE - Shilfa Nisa Agustin; Lutfi Adin Affandi (Jurnal Penelitian Progresif, 2026)
This literature review examines the causes, armament technology evolution, military strategies, and future projections of the Russia-Ukraine War (2022–present), one of Europe's largest conflicts since World War II. Drawing on historical, geopolitical, and technological analyses, the study addresses key questions: root causes of the invasion, temporal developments in weaponry (e.g., drones, artillery, EW systems), strategies employed by both sides including public involvement, and long-term implications. Data were collected through systematic review of peer-reviewed journals, think-tank reports (RUSI, ISW), and official documents (2021–2026). Findings highlight Russia's quantitative attrition approach versus Ukraine's asymmetric innovation and Western aid. The war accelerates drone swarms, AI integration, and electronic warfare, projecting prolonged attrition or frozen conflict with risks of regional escalation. Conclusions emphasize lessons for national defense strategies, particularly for archipelagic nations like Indonesia in hybrid warfare preparedness. This case underscores the interplay of technology, strategy, and societal resilience in modern conflicts.